A MIC-LSTM based parameter extraction method for single-diode PV model - Hao, Xiaobo; Liu, Pengcheng; Deng, Yanhui; Meng, Xiangjian (Frontiers in Energy Research, 2024)
In recent years, the installed capacity of renewable energy systems has been rapidly growth, with a particularly notable increase of photovoltaic(PV) power. Photovoltaic modules are the fundamental element of the PV system. Modeling and analyzing PV modules are essential to assessing the output performance and characteristics of PV system under complex operating conditions. However, the inconsistent decay rates of PV modules bring great challenges in PV system modeling. Therefore, precisely modeling decayed PV modules becomes an urgent issue. In this paper, a MIC-LSTM based parameter extraction method for single-diode PV model is proposed, which could achieve precise derivation of PV module model parameters under any decay rate by establishing the mapping relationship between the characteristics of the current-voltage (I-V) curve and the five unknown parameters in the photovoltaic module model.